Androgen- and estrogen-secreting adrenal cancers. - Cavlan, D; Bharwani, N; Grossman, A (2010)
Androgen-secreting adrenal cancers are extremely rare malignancies, accounting for only a tiny proportion of the total number of women presenting with signs of androgen excess. Estrogen-secreting adrenal cancers are rarer still. Understanding how these tumors work benefits from an appreciation of adrenal steroid biosynthesis, as it is said that secretion in cancers is an anarchic version of normal adrenal function. Selection of patients in whom we should have a high suspicion of a malignancy is vital, so that biochemical investigation and imaging is deployed appropriately. When an adrenal tumor is found to secrete androgens or estrogens to excess, it can be difficult to confirm that it is a cancer, as there is significant overlap in the secretory patterns and imaging appearances of benign and malignant disease. The most reliable indicator of malignancy in these tumors remains the presence of metastases. Treatment is essentially surgical, although the role of mitotane is one undergoing evaluation.